The bcl-2 gene and 14;18 translocation in lymphoproliferative disorders. - Pezzella, F; Mason, D (1990)
The 14;18 translocation is generally considered a good marker for follicular lymphomas and it has also been suggested that it is of prognostic significance in this disease. It has also been claimed that the bcl-2 protein can be detected by immunohistology only in lymphoma carrying t(14;18). We have raised antibodies to the bcl-2 protein and shown that expression of the protein is not specific for the translocation and have also demonstrated that there is no correlation between prognosis and the presence of the translocation. It is also evident that t(14;18) is present only in about two-thirds of follicular lymphoma patients (and is found in 20-30% of diffuse lymphomas).